Secure Communication and Information Exchange using Authenticated Ciphertext Policy Attribute-Based Encryption in Mobile Ad-hoc Network - Huda, Samsul; Sudarsono, Amang; Harsono, Tri (EMITTER International Journal of Engineering Technology, 2016)
MANETs are considered as suitable for commercial applications such as law enforcement, conference meeting, and sharing information in a student classroom and critical services such as military operations, disaster relief, and rescue operations. Meanwhile, in military operation especially in the battlefield in freely medium which naturally needs high mobility and flexibility. Thus, applying MANETs make these networks vulnerable to various types of attacks such aspacket eavesdropping, data disseminating, message replay, message modification, and especially privacy issue. In this paper, we propose a secure communication and information exchange in MANET with considering secure adhoc routing and secure information exchange. Regarding privacy issue or anonymity, we use a reliable asymmetric encryption which protecting user privacy by utilizing insensitive user attributes as user identity, CP-ABE (Ciphertext-Policy Attribute-Based Encryption) cryptographic scheme. We also design protocols to implement the proposed scheme for various battlefied scenarios in real evironment using embedded devices. Our experimental results showed that the additional of HMAC (Keyed-Hash Message Authentication Code) and AES (Advanced Encryption standard) schemes using processor 1.2GHz only take processing time about 4.452 ms,Â  we can confirm that our approach by using CP-ABE with added HMAC and AES schemes make low overhead.